Improvement of solubility and pharmacokinetic profile of hepatoprotector icariin through complexation with HP-γ-cyclodextrin - Ding, Yili; Yu, Bo; Zhou, Shuzhen; Ding, Charles; Zhang, Zhiyuan; Xu, Shufeng; Xu, Zhe (Frontiers in Pharmacology, 2023)
Icariin as a hepatoprotector from Herba epimedii can expand the cardiovascular and cerebral blood vessels, promote hematopoietic functions, enhance the immune system and show anti-liver tumor activities. However, its low solubility (0.02 mg/mL) limits its clinical applications as food and medical supplements. Through complexation with HP-γ-cyclodextrin by using a trace amount of water-soluble polymer, the water solubility of icariin was increased by 654 times, which is the best result to date for the water solubility study of icariin. In an in vitro pharmacokinetic study, the complexation increased the dissolution rate of icariin by 80 times, and the icariin complex can be 100% released in the first few minutes. Through complexation, in an in vivo dog pharmacokinetic study, the Cmax of icariin was increased about 5 times, the AUC0-120 was increased about 20 times and the clearance of icariin was changed from 11.17 L/h/kg to 0.65 L/h/kg. The half-life time was changed from 0.68 h to 6.38 h and the relative bioavailability was increased by nearly 20 times, indicating that less drug is needed for the same therapeutic effect by using the icariin complex, and the complex can be used as a potential potent hepatoprotector or anti-liver cancer drug.